Increasing Feeder PV Hosting Capacity by Regulating Secondary Circuit Voltages - Grazia Todeschini (2018 IEEE Power & Energy Society General Meeting (PESGM), 2018)
Voltage rise is one of the major concerns that limits the photovoltaic (PV) hosting capacity or the maximum amount of PV generation that a distribution circuit can accommodate. This paper examines the effectiveness of low-voltage distribution static compensators (LV-DSTATCOMs) in increasing the PV hosting capacity of distribution circuits by mitigating voltage rise. Stochastic analysis framework is used to determine the PV hosting capacity while an iterative placement technique is used to identify effective device locations. To provide insights on the optimal device size, number, and control settings, sensitivity analysis is carried out. The results show that, with appropriate size and control settings, installation of few LV-DSTATCOMs in a distribution circuit can significantly increase its PV hosting capacity. For the circuit under consideration, a set of 23 devices has increased the PV hosting capacity from 15% to 100% of the median day time peak load.